STREET-ROAD NETWORK IN THE CITY OF TASHKENT ABOUT DENSITY (Web of Technology: Multidimensional Research Journal, 2024)
The density of the street-road network of the city of Tashkent is compared to the large cities of Europe and other developed countries.